Revision of the South African genus Neopimus (Coleoptera: Staphylinidae: Paederinae) - Janák, Jiří (Zootaxa, 2019)
A revision of the south African genus Neopimus Özdikmen, Demir & Türkeş, 2008 is presented. Based on revision of the type and additional material, three species are recognised. The genus Neopimus is redescribed and all species are described or redescribed and illustrated, two of them for the first time: Neopimus capensis Janák, sp. nov., from Eastern Cape Province, South Africa and N. zulu Janák, sp. nov., from KwaZulu-Natal Province, South Africa. The distribution of the genus is mapped and a key of species is presented.